The Metric Dimension and Local Metric Dimension of Relative Prime Graph - Kuswandari, Inna; Fatmawati, Fatmawati; Utoyo, Mohammad Imam (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2020)
This study aims to determine the value of metric dimensions and local metric dimensions of relative prime graphs formed from modulo integer rings, namely . As a vertex set is and if and are relatively prime. By finding the pattern elements of resolving set and local resolving set, it can be shown the value of the metric dimension and the local metric dimension of graphs are and respectively, where is the number of vertices groups that formed multiple 2,3, … , and is the cardinality of set . This research can be developed by determining the value of the fractional metric dimension, local fractional metric dimension and studying the advanced properties of graphs related to their forming rings.Key Words : metric dimension; modulo ; relative prime graph; resolving set; rings.